PENGARUH SMS BANKING, MOBILE BANKING, FASILITAS AUTOMATED TELLER MACHINE (ATM) TERHADAP KEPUASAN NASABAH PADA PT BANK BRI UNIT RIMBO ILIR - Mayroza Wiska; Kelik Purwanto; Nadya Vitaloka (ADISAM PUBLISHER, 2023)
The purpose of this study was to determine and analyse the effect of the quality of SMS Banking, Mobile Banking, and Automatic Teller Machine (ATM) Facilities on customer satisfaction at PT. Bank BRI Unit Rimbo Ilir. This research is a type of quantitative research. The population in this study are customer who use SMS Banking, Mobile Banking, and Automatic Teller Machine (ATM) facilities at PT. Bank BRI Unit Rimbo Ilir. The sampling methods in this study usea non-probability sampling. The number of sampels in this study were 100 respondents, with a population of all customers of PT. Bank BRI Unit Rimgo Ilir that uses SMS Banking, Mobile Banking and ATM Facilities. The methods in this research are questionnaries and documentation studies. The data analysis method used descriptive statistical methods and quantitative. The data analysis method used descriptive statistical methods and quantitative methods, namely multiple linear regression analysis with a significant level of 0,05. F test results indicate that SMS Banking, Mobile Banking, and Automatic Teller Machine (ATM) facilities simultaneously have a positive and significant effect on customer satisfaction at PT. Bank BRI Unti Rimbo Ilir. Based on the coefficient of determination (R²) shows that the Adjusted R Square value 0,802 means 80,2%. Customer satisfaction factor can be explained by SMS Baning Mobile Banking, and Automatic Teller Machine (ATM) facilities. While the remaining 19,8% is explained by other factor that cannot be investigated this study.